2018
DOI: 10.1111/sltb.12445
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Suicide Ideation in the Military: The Independent Role of Aggression

Abstract: The purpose of this study was to examine the longitudinal relationship between aggression and suicide ideation when controlling for other externalizing (i.e., alcohol misuse and risk-taking) and internalizing (i.e., depression and sleep problems) risk factors in an active duty, military sample. Preexisting data from a longitudinal study were analyzed to assess the wellness of service members across the deployment cycle. Participants were 944 active duty service members (95% male, 48% between 18 and 24 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…Findings of this report are consistent with the emerging literature linking anger to suicidality (Ducasse et al, 2017; Hogstedt et al, 2018; Start et al, 2019). In a recent report, Hogstedt et al (2018) found that likelihood of completed suicide and suicide attempts over a 35‐year follow‐up were 2.1 and 2.8 times higher in male Swedish conscripts with severe anger symptoms versus those with no anger symptoms at index visit.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Findings of this report are consistent with the emerging literature linking anger to suicidality (Ducasse et al, 2017; Hogstedt et al, 2018; Start et al, 2019). In a recent report, Hogstedt et al (2018) found that likelihood of completed suicide and suicide attempts over a 35‐year follow‐up were 2.1 and 2.8 times higher in male Swedish conscripts with severe anger symptoms versus those with no anger symptoms at index visit.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent report, Hogstedt et al (2018) found that likelihood of completed suicide and suicide attempts over a 35‐year follow‐up were 2.1 and 2.8 times higher in male Swedish conscripts with severe anger symptoms versus those with no anger symptoms at index visit. Similarly, Start et al found that presence of anger/aggression in active duty service members was associated with fivefold greater likelihood of reporting SI (categorized as score ≥2 on suicide‐related item of the 9‐item Patient Health Questionnaire) (Start et al, 2019). Remarkably, associations of anger with these measures of suicidality were significant, even after controlling for the presence of psychiatric illnesses and severity of depressive symptoms in both these studies (Hogstedt et al, 2018; Start et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a school-based sample of rural Chinese adolescents, participants with high levels of total aggression had 4.31 times higher risk of suicidal ideation compared to subjects with low level of total aggression [ 14 ]. In a study of military service members in the USA, those reporting aggression were significantly more likely to report suicide ideation than those reporting no aggression [ 15 ]. On the other hand, the low back pain association with suicidal ideation found in the present study agrees with results of a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…In military and veteran personnel, problematic anger has been associated with mental health conditions, including posttraumatic stress disorder (PTSD [3,5];), unhealthy habits and unnecessary risk taking [6], as well as relationship dysfunction [7]. Problematic anger and aggression are also risk factors for intent to harm others [5], interpersonal violence [8] and suicide-related outcomes [9]. While there is evidence that problematic anger is a significant concern in the civilian community [10], it is particularly important to understand the extent of problematic anger in military personnel and veterans and the key factors that contribute to its development and expression.…”
Section: Introductionmentioning
confidence: 99%